ESTUDO ANALÍTICO E AVALIAÇÃO DA ATIVIDADE ANTIBACTERIANA DA MISTURA DOS ÓLEOS ESSENCIAIS DE FRUTOS DE Pimenta dioica Lindl E DOS GALHOS DE Aniba duckei Kostermans - Pereira, Alvaro Itauna Schalcher (2009)
Plants are an important source of biologically active products, many of which are on models for the synthesis of new drugs. With the increase of the indiscriminate use of antibiotics, bacteria resistant to conventional antimicrobial therapy have emerged and the essential oils are mentioned as an alternative to the problem. This work is promoted the extraction of essential oils of Pimenta dioica Lindl species (fruit) and duckei Aniba Kostermans (branches), the method of hydrodistillation using a Clevenger and their mixture in equal parts. The species Aniba duckei Kostermans, last classification of pau rosa Amazon, is a native species in the Amazon region, the family of Lauráceas. You can reach 30m in height. The type of vegetation occurring is tropical moist forest and land. Its essential oil is used in perfumery because of its high content of linalool. The plant species Pimenta dioica Lindl, popularly known as allspice, is a tree 6 to 15 m in height and belongs to the family of Mirtaceae and is home to Central America and western India. In Brazil, the plant is found in large scale in the State of Bahia and Recife. Its fruit contains an essential oil of great economic value in the international market due to high content of eugenol which is widely used in the chemical and pharmaceutical industries. After extraction, the mixture of oils were characterized by the following physical parameters: density (25 ° C), solubility in 70% ethanol, a refractive index (ND 25), color, appearance and odor. Furthermore, it was possible, the techniques of UV-Vis spectrophotometry, gas chromatography and mass spectrometry to identify with certainty the linalool and eugenol as major constituents of the mixture of essential oils. In applying the mixture of essential oils and standards of eugenol and linalool as antimicrobial agents using the Kirby-Bauer method for the bacteria Bacillus cereus, Chromobacterium violaceum, Enterococcus faecalis, Listeria monocytogenes, Salmonella Thyphi, Serratia marcescens and antibiotics ampicillin, cefotaxime, cefoxitin, erythromycin, gentamicin, novobiocin, penicillin, tetracycline and vancomycin, for comparison. You can see that the study of antimicrobial activity showed that the mixture of essential oils showed excellent activity against all bacteria tested, with the eugenol and linalool are the main responsible for this effectiveness. In this research we observed that the blend of essential oils is more efficient than the standards of eugenol and linalool and the antibiotics tested for the pathogen Listeria monocytogenes, Enterococcus faecalis, Chromobacterium violaceum. For Bacillus cereus, Serratia marcescens and Salmonella Thyphi the mixture was not more effective than the antibiotics Tetracycline, Erythromycin, Cefoxitin, cefotaxime, ampicillin and penicillin.